The Interplay between Digital Competencies and Information Literacy in Academic Writing Online Class during COVID-19 Pandemic (PLS-SEM Approach) - Lastika Ary Prihandoko (Makassar State University, 2021)
Abstract. Due to insufficient academic literacy competency, which consists of information literacy and digital competency, students face online learning barriers during the COVID-19 pandemic. In addition, in the 21st-century learning framework, digital competency has considered as an essential skill. This study examines the interplay between mastery of hardware & software, digital cooperation, digital security, mastery of digital development, and digital skills toward information literacy. They were randomly selected as respondents was a sample of 258 students from the ESP class who took academic writing in Papua's university. The data was analyzed using Smart PLS 3.0.0. in order to conduct exploratory factor analysis. The results show that digital competency correlates positively with digital cooperation, digital security, and digital development mastery. Meanwhile, hardware and software mastery have a positive association with digital cooperation. In addition, digital competency has positive correlation toward information literacy. The implications for academic staff and policymakers of the findings of this study are presented.Keywords: Exploratory Factor Analysis, Digital Competency, Information Literacy, Academic Writing, COVID-19